Analysis of the Use of Instagram Social Media by the Jambi Province General Election Commission as a Media for Political Socialization in the 2024 Election - Nur Aini Atika; Irzal Anderson; Hendra Hendra (Journal of Education Technology Information Social Sciences and Health, 2024)
The approach used by researchers is a descriptive qualitative approach. The data collection techniques used by researchers in this research are observation, interviews and documentation. And then the data analysis techniques used by researchers in this research are data collection, data reduction, data presentation and data verification. The results of this research can be concluded that Instagram social media has become a tool for the Jambi Province General Election Commission to use to spread political messages and build their image during the elections. Through popular and interactive accounts, they can reach a wider range of voters and interact directly with them. Features such as reach, views, hashtags, and location tagging allow political messages to spread more efficiently among a diverse electorate. In using the social media Instagram by the Jambi Provincial General Election Commission as a socialization medium, the General Election Commission must further increase interaction with the public apart from likes and comments. The General Election Commission can use QNA to make it easier for the public to interact and ask questions about what they do not understand. In implementing political outreach using the social media Instagram at the Jambi Province General Election Commission, there are several obstacles, namely the lack of a creative team specifically responsible for their field, not all groups know about the socialization carried out using Instagram, and community participation is not that great due to a lack of awareness in politics.